Letter from Campbell Morfit to James Curtis Booth, May 14, 1855 - Morfit, Campbell (1855)
Campbell Morfit (1820-1897), a distinguished chemist from the United States, co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry, writes to thank Booth for a loan and speaks at length about his wife's passing.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897